Multiobjective Optimization in Two-scale Thermoelastic Problems for Porous Solids - DŁUGOSZ, Adam; SCHLIETER, Tomasz (Engineering Transactions, 2016)
The multiobjective optimization of a two-scale thermoelastic problem is considered in this paper. To compute the solutions, direct thermoelastic analysis with the representative volume element (RVE) and the finite element method (FEM) analysis are performed. Evolutionary algorithms (EAs) are used to find a set of Pareto-optimal solutions. The design variables of the optimization problem are defined so as to describe the microstructure of a porous solid, whereas the optimization criteria are defined on the basis of macro-scale thermal and mechanical quantities. A numerical example of optimization is included.